2,4,5-Triaryl imidazole probes for the selective chromo-fluorogenic detection of Cu(II). Prospective use of the Cu(II) complexes for the optical recognition of biothiols - Okda, Hazem Essam (2019)
The sensing behaviour toward metal cations and biothiols of two 2,4,5-triarylimidazole probes (3a and 3b) is tested in acetonitrile and in acetonitrile-water. In acetonitrile the two probes present charge-transfer absorption bands in the 320-350 nm interval. Among all cations tested only Cu(11) is able to induce bathochromic shifts of the absorption band in the two probes, which is reflected in marked colour changes. Colour modulations are ascribed to the formation of 1:1 Cu(II)-probe complexes in which the cation interacts with the imidazole acceptor heterocycle. Besides, the two probes present intense emission bands (at 404 and 437 nm for 3a and 3b respectively) in acetonitrile that are quenched selectively by Cu(11). Probe 3a is soluble in acetonitrile-water 1:1 (v/v) and Cu(11) also induces bathochromic shifts of the absorption bands. Moreover, the emission bands of probe 3a in this mixed aqueous solutions is quenched in the presence of Cu(II). The potential use of the 1:1 complex formed between 3a and Cu (II) for the chromo-fluorogenic detection of biothiols (GSH, Cys and Hcy) in aqueous environments is also tested. At this respect, addition of GSH, Cys and Hcy to acetonitrile-water 1:1 v/v solutions of 3a-Cu(11) complex induces a hypsochromic shift of the visible band (reflected in a bleaching of the solutions) with a marked emission increase at 470 nm.